GAMBARAN KETERAMPILAN KADER DALAM PENGUKURAN BB DAN TB BERDASARKAN KARAKTERISTIK KADER DI WILAYAH KERJA PUSKESMAS LANGSA TIMUR PROVINSI ACEH TAHUN 2015 - Nurainun .; Fitri Ardiani; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
There are any cadre of Posyandu who have not skill in measurement of weight and high of body of child under five in dacin balancing before weighing the child under five. This is influenced by any factors such as education, knowledge, duration to be a cadre and training followed by the cadre.This research aims to study an overview of skill of cadre in measure the weigh and high of body of child under five in Posyandu in the work area of Puskesmas Langsa Timur Province  of Aceh.This research is a descriptive study by moment observation study. The data was collected by interview and observation when implement the Posyandu activities.Based on the research indicated that the skill of cadre in measurement of weight and height of child body under five was in poor  skill category for 59 cadres (62.1%). The higher education was in the category of graduate of senior high school (SMA) for 46 cadres (48.4%).  The cadre who has skill in  measurement  of  weight  and  height  of  body  with  graduation  of  DIII/S1  is  11  persons  (84. 62%). More  of  cadres  have  poor  knowledge  about  the  measurement  of  weight  and  height  of  body  for  41 cadres (43.2%). The cadres who have skill in measurement of weight and height of body with good knowledge  were  15  persons  (60%).  The  cadres  who  never  follow  any  training  were  70  cadres (73.7%). The cadres who have skill in measurement of weight and height of body are cadres who have follow training for 24 persons (96%). More of cadres with the duration time to be cadres were > 3 years for 49 cadres (51.6%). The  cadre who has skill in measurement of weight and height of body and has to be cadre during > 3 years was 23 persons (46.94%).It is suggested that Puskesmas design and hold training for cadres periodically to minimize the error in measurement that influence the nutrition status of child under five.Keywords  :    Characteristic  of  cadre,  Skill  of  cadre  in  measurement  of  weight  and Height of body